Nomenclatural notes on Pamphalea (Asteraceae: Nassauvieae) - Platt, Fernando Henrique; Bündchen, Márcia; Miotto, Silvia Teresinha Sfoggia (Phytotaxa, 2016)
As part of a study on Pamphalea conducted in the state of Rio Grande do Sul, Brazil, we present here the lectotypifications of P. bupleurifolia, P. cardaminifolia, P. ramboi and P. ramboi var. scaposa, as well as the synonymization of the latter and comments on the proper orthography of the generic name.